Identification of PDE10A related proteins via proteomic analysis (Annals of Medical Research, 2022)
Aim: Phosphodiesterase 10A (PDE10A) regulates the expression of secondary messengers of cyclic adenosine monophosphate and cyclic guanosine monophosphate, which control several intracellular signaling pathways. Recently, deactivation of PDE10A has been a notable target for the treatment of neurodegenerative diseases. Herein, we identified the effects of PDE10A inhibition on protein profile using TAK-063 under physiological conditions in mice.Materials and Methods: In this study, 8-12 weeks old male C57BL6/J mice were divided into vehicle or 3 mg/kg TAK-063 groups. Thirty minutes after oral delivery of vehicle or TAK-063, animals were sacrificed and liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS) mediated proteomic analyses were performed from tissue samples taken from the striatum region of mice. After the LC-MS/MS analysis, identified proteins were classified based on biological activity, molecular function, and signal transduction pathways using PANTHER (protein annotation through evolutionary relationship, http://www.pantherdb.org/) program.Results: As a result of proteomic analyses, 1873 different proteins were identified. Sixty-one different proteins changed significantly depending on the administration of TAK-063. Accarding to PANTHER classification, a significant part of the identified proteins found to be in the metabolite interconversion enzyme, transporter, and protein modifying enzyme category. The molecular function classification includes the catalytic activity, transporter activity, and binding functions. The signal transduction pathway analysis demonstrated that PDE10A affects ATP synthesis, FGF signaling, EGF receptor signaling, Huntington's Disease, Parkinson's Disease, pyrimidine metabolism, and ubiquitin-proteasome signal transduction pathways.Conclusion: TAK-063 mediated PDE10 deactivation is an essential target in the mechanism of energy metabolism and neurodegenerative diseases.